MARKETING MIX EFFECT ON CUSTOMER SATISFACTION ON THE TOURISM IN TOMOHON CITY - Untu, Victoria N.; Tielung, Maria V. (International Journal of Research -GRANTHAALAYAH, 2021)
Motivation/Background : Consumer satisfaction is very important for a tourist spot, because it determines the ability and level of profit it can achieve. Because it is necessary to pay attention to things that have the potential to affect consumer satisfaction, including the Marketing Mix. This study discusses the aspects of the marketing mix that affect consumer satisfaction at tourist attractions in the city of Tomohon. The aim is to determine the effect of the Marketing Mix on Customer Satisfaction. Marketing Mix (Marketing Mix) is a set of marketing tools that companies use to achieve goals in target markets. Marketing Mix includes variable Product (Product), Price (Price), Place (Place) and Promotion (Promotion). Consumer satisfaction is the feeling of pleasure or disappointment of a customer that arises after comparing perceptions of the performance of a product and its expectations. Method: In this study, the data collection techniques used were observation, interviews and a list of questions given to consumers or guests on the object under study. The variables measured are the factors of the marketing mix including product (X1), price (X2), place (X3) and promotion (X4), and customer satisfaction (Y). The analytical method used is Multiple Linear Regression Analysis. Results: From the analysis results obtained the value of the coefficient of determination (r 2 ) of 0.889; which shows that the factors of the Marketing Mix have a contribution or proportion of the contribution to the variation (fluctuation) of Consumer Satisfaction by 88.9%, while the remaining 11.1% is explained by other factors. Conclusions: From the research results, the value of the Correlation Coefficient (r) is 0.943 (94.3%) or close to 1 (100%), which indicates that there is a very close and positive relationship between the Marketing Mix and the Consumer Satisfaction.